Antibodies to Deamidated Gliadin Peptide in Diagnosis of Celiac Disease in Children. Issue 5 (May 2015) - Lammi, Anne; Arikoski, Pekka; Simell, Satu; Kinnunen, Tuure; Simell, Ville; Paavanen-Huhtala, Sari; Hinkkanen, Ari; Veijola, Riitta; Knip, Mikael; Toppari, Jorma; Vaarala, Outi; Simell, Olli; et al.
ABSTRACT Objectives: Determination of antibodies to synthetic deamidated gliadin peptides (anti-DGPs) may work as an alternative or complement the commonly used test for tissue transglutaminase antibodies (TGA) in the diagnosis of celiac disease (CD). We analyzed the performance of a time-resolved immunofluorometric anti-DGP assay (TR-IFMA) in the diagnosis of CD in children and also retrospectively analyzed the appearance of anti-DGP antibodies before TGA seroconversion. Methods: The study included 92 children with biopsy-confirmed CD. Serum samples were taken at the time or just before the clinical diagnosis. The control group comprised 82 TGA-negative children who were positive for human leucocyte antigen-DQ2 or -DQ8. Results: Based on receiver operating characteristic curves, the optimal cutoff value for immunoglobulin (Ig) A anti-DGP positivity was 153 arbitrary units (AUs) with a sensitivity of 92.4% and specificity of 97.6% and that for IgG anti-DGP 119 AU, with a sensitivity of 97.8% and specificity of 97.6%. All 92 children with CD were either IgA or IgG anti-DGP positive at the time of diagnosis. Sera from 48 children with CD were also analyzed retrospectively before the diagnosis. Anti-DGP antibodies preceded TGA positivity in 35 of the 48 children with CD and appeared a median of 1 year earlier. Conclusions: The TR-IFMA assay for detecting anti-DGP antibodies shows high sensitivity and specificity for the diagnosis of CD in children. In a majority of our study population, anti-DGP seropositivity preceded TGA positivity, indicating that earlier detection of CD may be possible by monitoring anti-DGP antibodies frequently in genetically susceptible children.